Bereaved Military Dependent Spouses and Children: Those Left Behind in a Decade of War (2001–2011). Issue 3 (1st March 2017) - Cozza, Stephen J.; Fisher, Joscelyn E.; Zhou, Jing; Harrington-LaMorie, Jill; La Flair, Lareina; Fullerton, Carol S.; Ursano, Robert J.
ABSTRACT: Background: U.S. military service members die from a variety of causes (i.e., accidents, combat, illnesses, homicide, suicide, and terrorism) while on duty and in greater numbers during times of war, leaving behind bereaved dependent family members. Identifying characteristics of these dependent families improves our understanding of their unique needs, helps educate service providers who offer assistance to these surviving family members, and better informs policy addressing their health and well-being. This study describes deceased U.S. military service members (DSMs) who died on active duty between September 11, 2001 and September 11, 2011 and their surviving dependent spouses and children. Methods: Characteristics of DSMs (service branch, rank, and cause of death) and characteristics of spouse-with-children and spouse-only families (ages of dependents, time since loss, and distance from a military installation) were examined. Results: 15, 938 DSMs died from a variety of causes (e.g., accidents, combat, and illnesses). 55% of DSMs had dependent spouses and 56% of those spouses had children. Most surviving dependent spouses and children were young (mean ages = 32.8, 10.3 years; SD = 9.3, 7.3 years, respectively) at the time of DSM death. Many of these young dependents were related to a DSM who experienced a sudden and violent death. 60% of spouse-with-children families and 58% of spouse-only families lived farther than 60 miles from a military installation. Time since loss (range = 1.3–11.3 years) did not predict distance to installation. Conclusions: Findings characterize surviving spouses and their children, suggest potential risk for problematic grief outcomes, and underscore the importance of educating service providers about how to support military survivor family health and resilience.